2023
DOI: 10.1021/acsomega.2c05546
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning C–N Couplings: Obstacles for a General-Purpose Reaction Yield Prediction

Abstract: Pd-catalyzed C−N couplings are commonplace in academia and industry. Despite their significance, finding suitable reaction conditions leading to a high yield, for instance, remains a challenging and time-consuming task which usually requires screening over many sets of conditions. To help select promising reaction conditions in the vast space of reagent combinations, machine learning is an emerging technique with a lot of promise. In this work, we assess whether the reaction yield of C−N couplings can be predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…To verify the effectiveness of the proposed RSTA mechanism, an indicator called the permutation variable importance (PVI) 40 was used to measure the importance of each input variable to the output variable. The PVI of an input variable is obtained by calculating the ratio between the prediction errors before and after the variable data are shuffled; only the data corresponding to the variable are shuffled each time.…”
Section: Statistical Analysis and Discussion On Variable Importancementioning
confidence: 99%
“…To verify the effectiveness of the proposed RSTA mechanism, an indicator called the permutation variable importance (PVI) 40 was used to measure the importance of each input variable to the output variable. The PVI of an input variable is obtained by calculating the ratio between the prediction errors before and after the variable data are shuffled; only the data corresponding to the variable are shuffled each time.…”
Section: Statistical Analysis and Discussion On Variable Importancementioning
confidence: 99%
“…On the other hand, a similar analysis on Buchwald− Hartwig C−N coupling reactions compiled from the literature suggests the opposite: using the entire data set improved the models. 62 At this point in time, recognizing a priori which approach is best is not a clearly defined task. Alternatively, multiple source data sets could be utilized for transfer learning, resembling the traditional approach where a chemist's source data contains just a handful of research articles.…”
Section: ■ Transfer Learningmentioning
confidence: 99%
“…This showed that for reactions defined using domain specific knowledge, modest predictivity is plausible using relatively small data sets, in this case about 100 data points. On the other hand, a similar analysis on Buchwald–Hartwig C–N coupling reactions compiled from the literature suggests the opposite: using the entire data set improved the models . At this point in time, recognizing a priori which approach is best is not a clearly defined task.…”
Section: Transfer Learningmentioning
confidence: 99%
“…However, there is not a “general catalytic system” and each reactant combination (aryl iodide/bromide/chloride and amine/amide/N-heterocycle/etc.) seems to require a specific copper source and a dedicated ligand . Furthermore, literature precedents mainly focus on relatively simple substrates, whereas examples of more challenging coupling partners typically found in discovery programs (e.g., sterically hindered, , containing multiple nitrogens which can chelate the metal center and inhibit its catalytic activity), are rarer.…”
Section: Introductionmentioning
confidence: 99%